Revising the Roads Investment Strategy in Rural Areas : An Application for Uganda - Raballand, Gaël (2012)
Based on extensive data collection in Uganda, this paper demonstrates that the rural access index, as defined today, should not be a government objective because the benefit of such investment is minimal, whereas achieving rural accessibility at less than 2 kilometers would require massive investments that are not sustainable. Taking into account the fact that plot size is limited on average to less than 1 hectare, a farmer s transport requirement is usually minimal and does not necessarily involve massive investments in infrastructure. This is because most farmers cannot fully load a truck or pay for this service and, even if productivity were to increase significantly, the production threshold would not be reached by most individual farmers. Therefore, in terms of public policy, maintenance of the existing rural roads rather than opening new roads should be given priority; the district feeder road allocation maintenance formula should be revised to take into account economic potential and, finally, policy makers should devote their attention to innovative marketing models from other countries where smallholder loads are consolidated through private-based consolidators.